2019
DOI: 10.3390/antibiotics8040205
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Potential of Seaweed Derived-Endophytic Fungi

Abstract: The marine environment presents a high biodiversity and a valuable source of bioactive compounds with therapeutic and biotechnological potential. Among the organisms present in marine environment, the endophytic fungi isolated from seaweed stand out. These microorganisms have aroused interest in the scientific community regarding its various activities such as antiviral, antimicrobial, antioxidant, photoprotective, cytotoxic, genotoxic, anti-inflammatory, and anticancer, besides establishing important ecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 111 publications
0
20
0
Order By: Relevance
“…They are also useful in the production of biosurfactants (Cicatiello et al, 2016;Pitocchi et al, 2020), enzymes (Nicoletti and Andolfi, 2018), and bioremediation (Bovio et al, 2017). Interestingly, endophytic fungi that are associated with macroalgae produce biologically active secondary metabolites with antibacterial, antifungal anticancer and other beneficial properties (Mathan et al, 2013;de Felício et al, 2015;Teixeira et al, 2019). Furthermore, marine fungal enzymes can be used for cleaning, textile, leather, biofuel, pulp, and paper industries; for food and beverages; for animal feed; for environmental, pharmaceutical and cosmetic applications (Bonugli-Santos et al, 2015).…”
Section: Fungimentioning
confidence: 99%
“…They are also useful in the production of biosurfactants (Cicatiello et al, 2016;Pitocchi et al, 2020), enzymes (Nicoletti and Andolfi, 2018), and bioremediation (Bovio et al, 2017). Interestingly, endophytic fungi that are associated with macroalgae produce biologically active secondary metabolites with antibacterial, antifungal anticancer and other beneficial properties (Mathan et al, 2013;de Felício et al, 2015;Teixeira et al, 2019). Furthermore, marine fungal enzymes can be used for cleaning, textile, leather, biofuel, pulp, and paper industries; for food and beverages; for animal feed; for environmental, pharmaceutical and cosmetic applications (Bonugli-Santos et al, 2015).…”
Section: Fungimentioning
confidence: 99%
“…The association between the host and its endophytic fungi displays symbiotic features as the endophytic inhabitant frequently gains nutrients from the host and in return strongly promotes algal growth and improves its fitness through producing definite efficient metabolites [ 42 ]. Several species of macroalgae have been tested universal in relation to their connected fungal populations, which contains different genera since the union concerning fungi and marine algae stimulates the biosynthesis of metabolites with curative possibility by these fungi [ 72 ]. Amongst these metabolites, the most frequently isolated chemical classes are peptides, polyketides, lactones, alkaloids and terpenes.…”
Section: Main Textmentioning
confidence: 99%
“…Fungi, which are classified as eukaryotes, are also included in microorganisms in a broad sense. In recent decades, it has been reported that microorganism-derived compounds have various bioactivities including antioxidant and antitumor effects [17,18] (Table 1). According to studies, microorganism derived compounds induced cell cycle arrest at the G2/M phase and inhibited tubulin assembly; subsequently, it triggered apoptosis in colon cancer cells [19].…”
Section: Microorganism-derived Compounds and Lymphomamentioning
confidence: 99%